Types of finish lines and preparations for full and partial dental crowns: clinical considerations. A literature review - Plaza Plaza , Stephanie Patricia (2025)
Restorations with dental crowns are an established practice for reconstructing teeth in poor condition, providing essential basic functions. Currently, there are several materials for dental crowns, chosen according to the function of each piece, from aesthetic crowns to crowns with metal alloys. Tooth preparation, especially the finish line, is crucial to ensure the strength and longevity of the crown, avoiding short- and long-term failures. Additionally, it is essential to have a good clinical history to identify problems, such as those related to the temporomandibular joint, that should be treated before crown placement. There are different types of finishing lines, each with specific applications and advantages: 90° straight shoulder: Ideal for full ceramic crowns, it offers good resistance but requires greater tooth wear; rounded shoulder: it improves the direction of chewing forces and provides better cement exit, promoting adhesion; deep chamfer: it provides adequate space for metal or ceramic, improving cement exit and adaptation; light-superficial chamfer: similar to the deep chamfer, but preserves more of the dental remnant, indicated for metal-acrylic and metal-porcelain crowns. For partial crowns, such as porcelain veneers, less invasive finishing lines, such as the beveled edge, are preferred, preserving more tooth tissue and improving the patient's aesthetics. In ceramic restorations, advanced materials such as glass-ceramic and lithium disilicate are preferred for their strength and aesthetic properties. Correct adaptation and tooth preparation are essential for the long-term success of restorations.